Trinidad. War Memorial - Power (Davidson and Todd Ltd., Trinidad, 2010)
Here is a photograph of the war monument at War Memorial Park showing many of its details. The moulding, on the upper part of the monument, looks like fancy cake decorations. The statues near the middle of are of soldiers in action and on the top is a large angel. The monument was placed here in honour of Trinidad and Tobago nationals who served and died in World Wars I and II, 1914-1918 and 1939-1945. The four steps at the base are obscured from view by several colourful wreaths. A number of men: some in uniform; others in suits or civilian clothing, have gathered around the monument. There are palms and historic buildings in the background. Postcard No. 11.
Colour: Coloured; Style: Portrait; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; War memorials--Trinidad and Tobago; Monuments--Trinidad and Tobago; Memorials--Trinidad and Tobago; Statues--Trinidad and Tobago; Buildings--Trinidad and Tobago; Palms--Trinidad and Tobago; Men--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Wreaths--Trinidad and Tobago; Parks--Trinidad and Tobago; World War, 1914-1918--Monuments--Trinidad and Tobago; World War, 1939-1945--Monuments--Trinidad and Tobago; War Memorial Park (Port of Spain)